Radio Frequency Identification (RFID) Implementation for Human Tracking in Safety Management at Construction Site - Lim, Jyy Chyi; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam (Research in Management of Technology and Business, 2022)
The construction industry in Malaysia faces safety and health problem due to poor safety management and inaccurate positioning and tracking issue. RFID is currently being used in many industries, such as production, healthcare, transportation, and tracking applications, especially in supply chain management. However, Radio Frequency Identification (RFID) has not been widely used in the construction industry. Therefore, this research was conducted to identify the potential, barriers, and improvement ways of Radio Frequency Identification (RFID) implementation for human tracking in safety management at the construction site. To achieve the objectives, the research was conducted using quantitative methods for primary data collection and questionnaires as the instrument. There were 254 G7 contractor target respondents from Johor, who were selected to obtain information from this research. The data were analyzed through SPSS software to determine the mean and standard deviation, and through Microsoft Excel to generate pie charts and bar for the respondents’ background to get the frequency and percentage values. The results showed that RFID has the potential to capture real-time information of workers on-site and rescue injured people faster for human tracking systems. The biggest barrier to RFID implementation was a lack of understanding of RFID technology among construction workers. The highest rank for the key improvement ways was top management’s need to promote the RFID technology for a human tracking system in safety management. In conclusion, the research provided a great deal of knowledge for effective safety management with RFID implementation in human tracking at the construction site.